Green Dyeing and Antibacterial Treatment of Hemp Fabrics Using Punica granatum Peel Extracts. (12th August 2020) - Inprasit, Thitirat; Pukkao, Jarinphorn; Lertlaksameephan, Nattanee; Chuenchom, Araya; Motina, Kanjana; Inprasit, Worapat
Abstract : In this study, the dyeing performance and antibacterial properties of pomegranate ( Punica granatum ) peel extracts were investigated, when applied to hemp fabric. A tannin-rich natural dye was extracted using water at 100°C. As the antibacterial agent was sensitive to temperature, it was extracted using Soxhlet apparatus with methanol at 55°C. The color strength (K / S ) values were investigated and found to increase in line with the dye concentration, dyeing time, and temperature. Optimal dyeing of the hemp fabric was achieved when applying 6% w / v of extract at 80°C for 60 min. This produced a yellowish-brown appearance. The dyed fabrics were rated as good to excellent for color fastness against washing, water, sea water, and perspiration. The dyed fabrics were next finished with the antibacterial agent extracted from the peel and tested for activity against Staphylococcus aureus (Gram positive) and Klebsiella pneumoniae (Gram negative), using the AATCC-100 (percentage reduction) test. The fabric was demonstrated to be 99.99% effective against Staphylococcus aureus, and this was conserved across 20 wash cycles.